A Study on Size and Shape of Plots for Grass Surveys - Negi, G. S.; Rawat, D. S. (Indian Forester, 1971)
The paper presents the results of a pilot investigation on the size and shape of plots for grass land survey, conducted in Andhra Pradesh. The results based on systematic line plot survey indicate that square or circular plots of 4 square metres may provide equally precise estimates as larger sized plots in such areas. It has been suggested that estimate of grass yield within 10% margin of error may be obtained with a sample of about 70 plots. Systematic sampling with multiple random start has been recommended.